Soil concentrations and soil-atmosphere exchange of alkylamines in a boreal Scots pine forest - Kieloaho, Antti-Jussi; Pihlatie, Mari; Launiainen, Samuli; Kulmala, Markku; Riekkola, Marja-Liisa; Parshintsev, Jevgeni; Mammarella, Ivan; Vesala, Timo; Heinonsalo, Jussi (Copernicus Gesellschaft MBH, 2017)
Alkylamines are important precursors in secondary aerosol formation in the boreal forest atmosphere. To better understand the behavior and sources of two alkylamines, dimethylamine (DMA) and diethylamine (DEA), we estimated the magnitudes of soil-atmosphere fluxes of DMA and DEA using a gradient-diffusion approximation based on measured concentrations in soil solution and in the canopy air space. The ambient air concentration of DMA used in this study was a sum of DMA and ethylamine. To compute the amine fluxes, we first estimated the soil air space concentration from the measured soil solution amine concentration using soil physical (temperature, soil water content) and chemical (pH) state variables. Then, we used the resistance analogy to account for gas transport mechanisms in the soil, soil boundary layer, and canopy air space. The resulting flux estimates revealed that the boreal forest soil with a typical long-term mean pH 5.3 is a possible source of DMA (170 +/- 51 nmolm(-2) day(-1)) and a sink of DEA (-1.2 +/- 1.2 nmolm(-2) day(-1)). We also investigated the potential role of fungi as a reservoir for alkylamines in boreal forest soil. We found high DMA and DEA concentrations both in fungal hyphae collected from field humus samples and in fungal pure cultures. The highest DMA and DEA concentrations were found in fungal strains belonging to decay and ectomycorrhizal fungal groups, indicating that boreal forest soil and, in particular, fungal biomass may be important reservoirs for these alkylamines.
Keywords: alkylamines; dimethylamine (DMA); diethylamine (DEA); volatile organic compounds; aerosol particles; amiinit; amines